Formal techniques for safety-critical systems : 5th International Workshop, FTSCS 2016, Tokyo, Japan, November 14, 2016, Revised selected papers /: 5th International Workshop, FTSCS 2016, Tokyo, Japan, November 14, 2016, Revised selected papers. (2017) - Unknown
No abstract available